Full-self-repairing anti-corrosion coating with high strength, long-term durability and excellent self-healing capacity and preparation method of full-self-repairing anti-corrosion coating

By building a double-layer coating structure based on high-performance hyperbranched polyurea and combining the bond exchange principle of dynamic bonds, the problem of difficult balance between barrier and self-repairing ability of self-repair coating in the prior art is solved, and a fully self-repair anti-corrosion coating with high strength, long-term durability and excellent self-healing ability is achieved.

CN119684882APending Publication Date: 2025-03-25MIANYANG MAXWELL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411878463.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing self-healing coatings are difficult to balance between barrier capacity and self-healing capacity, resulting in corrosion problems easily occur during long-term use.

Method used

Using a double-layer coating structure, the self-healing base layer is prepared by mixing zinc powder and hyperbranched polyurea. The self-healing anti-corrosion surface layer is formed by free radical polymerization of polyetheramine and acrylate fluoropolymer, and the bond exchange principle of dynamic bonds is combined to achieve rapid self-healing.

Benefits of technology

It achieves a fully self-repair anti-corrosion coating with high strength, long-term durability and excellent self-healing ability. It can quickly repair scratches at room temperature, maintain excellent barrier and corrosion resistance, and extend the service life of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119684882A_ABST
    Figure CN119684882A_ABST
Patent Text Reader

Abstract

The invention provides a full-self-repairing anticorrosive coating with high strength, long-term durability and excellent self-healing capability and a preparation method thereof, and belongs to the technical field of high polymer materials and preparation. According to the invention, the concept of full repair is provided for the first time: 1) zinc powder and polyurea with a hyperbranched structure are mixed to prepare a self-repairing bottom layer, so that the purpose of anode sacrifice and cathode protection is achieved; 2) polyurea with a hyperbranched structure is grafted with a fluorine-containing polymer, so that the aim of blocking is fulfilled; and (3) the active anti-corrosion bottom layer is combined with the passive anti-corrosion surface layer, so that the full-self-repairing purpose is achieved, and the full-self-repairing anti-corrosion coating with high adhesion and high durability is obtained. The self-repairing of the polyurea elastomer with the hyperbranched structure is realized by utilizing the bond exchange principle of dynamic bonds, the scratch repairing time is only 3.5 hours, and the strength is higher (21.5 MPa). The coating can resist mechanical damages such as water flushing, scratches and the like and has good durability in high-salt and high-humidity environments, and the service life of the coating is greatly prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of polymer materials and preparation technology, and in particular to a fully self-repairing anti-corrosion coating with high strength, long-term durability and excellent self-healing ability and a preparation method thereof. Background Art

[0002] In industrial production and daily life, metal corrosion can cause serious environmental pollution and safety hazards. Coating anti-corrosion is one of the most economical and effective means. Traditional coatings cannot be repaired after being damaged, and it is difficult to achieve long-term corrosion protection. Self-repairing coatings can re-establish a protective barrier after the coating is damaged, which is an effective way to extend the service life of metals.

[0003] Self-healing coatings are divided into intrinsic self-healing and external self-healing according to whether external repair agents are required. Intrinsic self-healing ability can be achieved by introducing reversible dynamic bonds, (a) dynamic covalent bonds; (b) dynamic non-covalent interactions. Polyurea coatings have better mechanical properties and adhesion than other coatings due to their internal chemical bonds (such as urea bonds and intramolecular hydrogen bonds), and they have higher density and better anti-corrosion performance.

[0004] The application of self-repairing in anti-corrosion coatings generally includes two types. One is to directly use the self-repairing layer as an anti-corrosion coating. They lack satisfactory barrier ability. Under long-term contact with the anti-corrosion medium, the corrosive medium will inevitably enter the coating and cause metal corrosion. In recent years, although there have been reports of using photothermal methods for coating self-repair, the coating will soften when heated, destroying the mechanical properties. Another method is to combine the self-repairing layer with other anti-corrosion layers. For example: the self-repairing layer is combined with other anti-corrosion layers such as the anodic protection layer and the barrier layer. Although the anti-corrosion performance of the coating has been improved, the self-repairing ability has been sacrificed. Therefore, how to balance self-repairing and barrier capabilities remains a huge challenge.

[0005] Therefore, in view of the problems existing in the existing technology, it is necessary to design a new type of high-strength, fully self-repairing anti-corrosion coating with long-term durability and excellent self-healing ability. Summary of the invention

[0006] The purpose of the present invention is to provide a fully self-repairing anti-corrosion coating with high strength, long-term durability and excellent self-healing ability and a preparation method thereof, so as to solve the above-mentioned technical problems.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] The present invention provides a method for preparing a fully self-repairing anti-corrosion coating with high strength, long-term durability and excellent self-healing ability. The fully self-repairing anti-corrosion coating with high strength, long-term durability and excellent self-healing ability comprises a self-repairing bottom layer and a self-repairing anti-corrosion surface layer. The preparation method comprises the following steps:

[0009] 1) dissolving polyetheramine, polyethyleneimine, tris(2-aminoethyl)amine and polyvinyl alcohol in an organic solvent, and then adding an isocyanate curing agent to carry out a condensation polymerization reaction to obtain a first product PUE;

[0010] 2) dissolving the first product PUE in an organic solvent to obtain a first dissolved substance solution;

[0011] 3) mixing the first dissolved substance solution with zinc powder to obtain a second dissolved substance solution;

[0012] 4) coating the second dissolved substance solution on the substrate, and obtaining a self-repairing bottom layer after curing;

[0013] 5) mixing the first product PUE and the acrylic ester fluorine-containing polymer in an organic solvent, and then adding an initiator to carry out a free radical polymerization reaction to obtain a second product PUEF;

[0014] 6) dissolving the second product PUEF in an organic solvent to obtain a third dissolved substance solution;

[0015] 7) The third dissolved substance solution is coated on the base layer, and after curing, a self-repairing anti-corrosion surface layer is obtained.

[0016] Further, the polyetheramine comprises polyetheramine D400 and polyetheramine D2000;

[0017] The acrylate fluorine-containing polymer is obtained by free radical polymerization of fluorine-containing acrylate monomers and acrylate monomers in the presence of an initiator;

[0018] The fluorine-containing acrylate monomer is 2,2,3,3,4,5,5,6,6,7,7-dodecafluoroheptyl acrylate, and the acrylate monomer comprises one of ethyl acrylate, methyl methacrylate and butyl acrylate;

[0019] The isocyanate curing agent includes isophorone diisocyanate.

[0020] Furthermore, the mass ratio of the polyetheramine, polyethyleneimine, tri(2-aminoethyl)amine and polyvinyl alcohol is 9000-10000:3-45:3-45:100-200, and the mass ratio of the isocyanate curing agent and the polyetheramine is 4-6:5-20.

[0021] Furthermore, the temperature of the free radical polymerization reaction is independently 60 to 80° C., and the reaction time is independently 20 to 28 hours.

[0022] Further, the organic solvent independently comprises one or more of 1,4-dioxane, cyclohexanone, tetrahydrofuran, ethanol and propylene glycol methyl ether;

[0023] The solid content of the first product PUE is 30-40%;

[0024] The solid content of the second product PUEF is 30-40%.

[0025] Furthermore, the solid content of the first solute solution is 30-40%, and the solid content of the third solute solution is 30-40%; the amount of the zinc powder added is 50-70% of the mass of the first product PUE.

[0026] Furthermore, the coating is spraying, and the thickness of the self-repairing bottom layer and the self-repairing anti-corrosion surface layer are independently 50 to 155 μm.

[0027] Furthermore, the mass ratio of the first product PUE to the acrylate fluorinated polymer is 10:30-50, and the content of the initiator is 0.2-1% of the mass of the acrylate fluorinated polymer;

[0028] The initiator comprises azobisisobutyronitrile and / or dibenzoyl peroxide.

[0029] Furthermore, the curing is performed at room temperature, and the curing time is 2 to 7 days.

[0030] The present invention also provides a fully self-repairing anti-corrosion coating with high strength, long-term durability and excellent self-healing ability.

[0031] Beneficial effects of the present invention:

[0032] The present invention constructs a double-layer coating based on high-performance hyperbranched polyurea. The self-repairing anodic protection primer and the hydrophobic topcoat provide rapid self-repairing capabilities while also providing excellent barrier and anti-corrosion capabilities, thereby constructing a fully self-repairing anti-corrosion coating with good performance, room temperature self-repairing capabilities, and long-term durability.

[0033] The present invention also has the following beneficial effects: (1) The present invention utilizes the dynamic exchange principle of intermolecular hydrogen bonds to achieve rapid self-repair of the polyurea elastomer, thereby resisting damage such as impact and extending the service life of the coating.

[0034] (2) The present invention can use a spraying method to prepare a fully self-repairing anti-corrosion coating on a substrate, which is simple and easy to operate. A framework of a fully self-repairing anti-corrosion coating with high impedance, high durability and stability, and high adhesion and room temperature self-repairing capability is constructed.

[0035] (3) The preparation process of the present invention is simple, the process is simple, easy to operate, and the product performance is good. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1Optical microscope images of the self-repair of the elastomer PUE of different proportions after scratching in Example 1;

[0037] Figure 2 This is an optical microscope image of the self-repairing bottom layer (PUEZ60) of Example 1 after scratching;

[0038] Figure 3 The optical microscope image and contact angle image of the self-repairing anti-corrosion surface layer after scratching after chemical modification in Example 1;

[0039] Figure 4 This is an optical microscope image of the self-repairing of the fully self-repairing anti-corrosion coating of Example 1 after a large-size (270 μm) scratch. DETAILED DESCRIPTION

[0040] The present invention provides a method for preparing a fully self-repairing anti-corrosion coating with high strength, long-term durability and excellent self-healing ability. The fully self-repairing anti-corrosion coating with high strength, long-term durability and excellent self-healing ability comprises a self-repairing bottom layer and a self-repairing anti-corrosion surface layer. The preparation method comprises the following steps:

[0041] 1) dissolving polyetheramine, polyethyleneimine, tris(2-aminoethyl)amine and polyvinyl alcohol in an organic solvent, and then adding an isocyanate curing agent to carry out a condensation polymerization reaction to obtain a first product PUE;

[0042] 2) dissolving the first product PUE in an organic solvent to obtain a first dissolved substance solution;

[0043] 3) mixing the first dissolved substance solution with zinc powder to obtain a second dissolved substance solution;

[0044] 4) coating the second dissolved substance solution on the substrate, and obtaining a self-repairing bottom layer after curing;

[0045] 5) mixing the first product PUE and the acrylic ester fluorine-containing polymer in an organic solvent, and then adding an initiator to carry out a free radical polymerization reaction to obtain a second product PUEF;

[0046] 6) dissolving the second product PUEF in an organic solvent to obtain a third dissolved substance solution;

[0047] 7) The third dissolved substance solution is coated on the base layer, and after curing, a self-repairing anti-corrosion surface layer is obtained.

[0048] In the present invention, the polyetheramine comprises polyetheramine D400 and polyetheramine D2000, and the mass ratio of the polyetheramine D400 to the polyetheramine D2000 is 5 to 10:5, preferably 6:5.

[0049] In the present invention, the acrylate fluorine-containing polymer comprises a fluorine-containing acrylate monomer and an acrylate monomer obtained by free radical polymerization in the presence of an initiator, the fluorine-containing acrylate monomer is 2,2,3,3,4,5,5,6,6,7,7-dodecafluoroheptyl acrylate, the acrylate monomer comprises one of ethyl acrylate, methyl methacrylate and butyl acrylate, and the acrylate fluorine-containing polymer is preferably polyethyl acrylate dodecafluoroheptyl ester.

[0050] In the present invention, the isocyanate curing agent is preferably isophorone diisocyanate.

[0051] In the present invention, the mass ratio of the polyetheramine, polyethyleneimine, tri(2-aminoethyl)amine and polyvinyl alcohol is 9000-10000:3-45:3-45:100-200, preferably 10000:9:9:200; the mass ratio of the isocyanate curing agent and the polyetheramine is 4-6:5-20, preferably 4.2-5.5:10-15, and more preferably 4.2:11.

[0052] In the present invention, the temperature of the free radical polymerization reaction is independently 60-80°C, preferably 65-75°C, and more preferably 70°C; the reaction time is independently 20-28h, preferably 22-26h, and more preferably 24h.

[0053] In the present invention, the organic solvent independently comprises one or more of 1,4-dioxane, cyclohexanone, tetrahydrofuran, ethanol and propylene glycol methyl ether, preferably 1,4-dioxane and cyclohexanone.

[0054] In the present invention, the solid content of the first product PUE is 30-40%, preferably 32-38%, and more preferably 34-36%; the solid content of the second product PUEF is 30-40%, preferably 32-38%, and more preferably 34-36%.

[0055] In the present invention, the solid content of the first solute solution is 30-40%, preferably 32-38%, and more preferably 34-36%; the solid content of the third solute solution is 30-40%, preferably 32-38%, and more preferably 34-36%; the amount of zinc powder added is 50-70% of the mass of the first product PUE, preferably 55-65%, and more preferably 60%.

[0056] In the present invention, the coating is spraying, and the thickness of the self-repairing bottom layer and the self-repairing anti-corrosion surface layer are independently 50-155 μm, the thickness of the self-repairing bottom layer is preferably 100 μm, and the thickness of the self-repairing anti-corrosion surface layer is preferably 50 μm.

[0057] In the present invention, the mass ratio of the first product PUE to the acrylate fluorinated polymer is 10:30-50, preferably 10:40; the content of the initiator is 0.2-1% of the mass of the acrylate fluorinated polymer, preferably 0.5%;

[0058] The initiator comprises azobisisobutyronitrile and / or dibenzoyl peroxide, preferably azobisisobutyronitrile.

[0059] In the present invention, the curing is room temperature curing, and the curing time is 2 to 7 days, preferably 5 days.

[0060] The present invention also provides a fully self-repairing anti-corrosion coating with high strength, long-term durability and excellent self-healing ability.

[0061] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0062] Example 1

[0063] 1) Mix and stir the raw materials such as polyetheramine D400 (6g), D2000 (5g), polyethyleneimine PEI (0.09g), tri(2-aminoethyl)amine (0.09g), polyvinyl alcohol (2g) and solvent (1,4-dioxane) (15g) evenly, then slowly drop isophorone diisocyanate IPDI (4.2g) and react in a 70°C oil bath for 24 hours. Free radical polymerization occurs, the solid is dissolved in 10mL tetrahydrofuran and washed three times with petroleum ether. The solvent is removed by rotary evaporation under reduced pressure, and then vacuum dried again at 50°C to obtain the first product, viscoelastic solid hyperbranched polyurea PUE;

[0064] 2) dissolving the first product PUE in tetrahydrofuran (THF) to obtain a first dissolved substance solution with a solid content of 33%;

[0065] 3) mixing the first dissolved substance solution with zinc powder to obtain a second dissolved substance solution, wherein the zinc powder content is 50% of the mass of the first product PUE;

[0066] 4) using a spray gun to evenly spray the second dissolved substance solution on the carbon steel sheet substrate, and curing it at room temperature for 2 days to obtain a self-repairing bottom layer with a thickness of 100 μm;

[0067] 5) Take the first product PUE (10 g) and the acrylic ester fluorinated polymer (40 g), dissolve them in 1,4-dioxane / cyclohexanone (100 g), add initiator AIBN (0.2 g), react in a 70° C. oil bath for 24 hours, and free radical polymerization occurs to obtain the second product PUEF;

[0068] 6) dissolving the second product in tetrahydrofuran (THF) to obtain a third dissolved substance solution having a solid content of 35%;

[0069] 7) The third dissolve solution is evenly sprayed on the self-repairing bottom layer with a spray gun and cured at room temperature for 7 days to obtain a fully self-repairing anti-corrosion coating with high strength, long-term durability and excellent self-healing ability. After the coating is cured, the total thickness of the coating is measured with a coating thickness gauge, and the total thickness of the coating is 150 μm.

[0070] Example 2

[0071] 1) Mix and stir the raw materials such as polyetheramine D400 (6g), D2000 (3.8g), polyethyleneimine PEI (0.08g), tri(2-aminoethyl)amine (0.08g), polyvinyl alcohol (2g) and 1,4-dioxane / cyclohexanone (15g) evenly, then slowly drop isophorone diisocyanate IPDI (4g) and react in a 70°C oil bath for 24 hours. Free radical polymerization occurs, the solid is dissolved in 10mL tetrahydrofuran and washed three times with petroleum ether. The solvent is removed by rotary evaporation under reduced pressure, and then vacuum dried again at 50°C to obtain the first product, viscoelastic solid hyperbranched polyurea PUE;

[0072] 2) dissolving the first product PUE in tetrahydrofuran (THF) to obtain a first dissolved substance solution with a solid content of 35%;

[0073] 3) mixing the first dissolved substance solution with zinc powder to obtain a second dissolved substance solution, wherein the zinc powder content is 55% of the mass of the first product PUE;

[0074] 4) using a spray gun to evenly spray the second dissolved substance solution on the carbon steel sheet substrate, and curing it at room temperature for 2 days to obtain a self-repairing bottom layer with a thickness of 100 μm;

[0075] 5) Take the first product PUE (10 g) and the acrylic ester fluorinated polymer (35 g), dissolve them in 1,4-dioxane / cyclohexanone (100 g), add initiator AIBN (0.3 g), react in a 70° C. oil bath for 24 hours, and free radical polymerization occurs to obtain the second product PUEF;

[0076] 6) dissolving the second product in tetrahydrofuran (THF) to obtain a third dissolved substance solution having a solid content of 35%;

[0077] 7) The third dissolve solution is evenly sprayed on the self-repairing bottom layer with a spray gun and cured at room temperature for 7 days to obtain a fully self-repairing anti-corrosion coating with high strength, long-term durability and excellent self-healing ability. After the coating is cured, the total thickness of the coating is measured with a coating thickness gauge, and the total thickness of the coating is 150 μm.

[0078] Example 3

[0079] 1) Mix and stir the raw materials such as polyetheramine D400 (5g), D2000 (5g), polyethyleneimine PEI (0.09g), tri(2-aminoethyl)amine (0.09g), polyvinyl alcohol (2g) and propylene glycol methyl ether (15g) evenly, then slowly drop isophorone diisocyanate IPDI (5.0g) and react in a 70°C oil bath for 24 hours. Free radical polymerization occurs, and the solid is dissolved in 10mL of tetrahydrofuran and washed three times with petroleum ether. The solvent is removed by rotary evaporation under reduced pressure, and then vacuum dried again at 50°C to obtain the first product, viscoelastic solid hyperbranched polyurea PUE;

[0080] 2) dissolving the first product PUE in tetrahydrofuran (THF) to obtain a first dissolved substance solution with a solid content of 40%;

[0081] 3) mixing the first dissolved substance solution with zinc powder to obtain a second dissolved substance solution, wherein the zinc powder content is 60% of the mass of the first product PUE;

[0082] 4) using a spray gun to evenly spray the second dissolved substance solution on the carbon steel sheet substrate, and curing it at room temperature for 2 days to obtain a self-repairing bottom layer with a thickness of 100 μm;

[0083] 5) Take the first product PUE (10 g) and the acrylic ester fluorinated polymer (42 g), dissolve them in 1,4-dioxane / cyclohexanone (100 g), add the initiator BPO (0.2 g), react in a 70° C. oil bath for 24 hours, and free radical polymerization occurs to obtain the second product PUEF;

[0084] 6) dissolving the second product in tetrahydrofuran (THF) to obtain a third dissolved substance solution having a solid content of 35%;

[0085] 7) The third dissolve solution is evenly sprayed on the self-repairing bottom layer with a spray gun and cured at room temperature for 7 days to obtain a fully self-repairing anti-corrosion coating with high strength, long-term durability and excellent self-healing ability. After the coating is cured, the total thickness of the coating is measured with a coating thickness gauge, and the total thickness of the coating is 150 μm.

[0086] Example 4

[0087] 1) Mix and stir the raw materials such as polyetheramine D400 (6g), D2000 (4g), polyethyleneimine PEI (0.045g), tri(2-aminoethyl)amine (0.045g), polyvinyl alcohol (2g) and tetrahydrofuran (15g) evenly, then slowly drop isophorone diisocyanate IPDI (4.2g) and react in a 70°C oil bath for 24 hours. Free radical polymerization occurs, the solid is dissolved in 10mL tetrahydrofuran and washed three times with petroleum ether. The solvent is removed by rotary evaporation under reduced pressure, and then vacuum dried again at 50°C to obtain the first product, viscoelastic solid hyperbranched polyurea PUE;

[0088] 2) dissolving the first product PUE in tetrahydrofuran (THF) to obtain a first dissolved substance solution with a solid content of 35%;

[0089] 3) mixing the first dissolved substance solution with zinc powder to obtain a second dissolved substance solution, wherein the zinc powder content is 58% of the mass of the first product PUE;

[0090] 4) using a spray gun to evenly spray the second dissolved substance solution on the carbon steel sheet substrate, and curing it at room temperature for 2 days to obtain a self-repairing bottom layer with a thickness of 100 μm;

[0091] 5) Take the first product PUE (10 g) and the acrylic ester fluorinated polymer (40 g), dissolve them in 1,4-dioxane / cyclohexanone (100 g), add the initiator BPO (0.3 g), react in a 70° C. oil bath for 24 hours, and free radical polymerization occurs to obtain the second product PUEF;

[0092] 6) dissolving the second product in tetrahydrofuran (THF) to obtain a third dissolved substance solution having a solid content of 35%;

[0093] 7) The third dissolve solution is evenly sprayed on the self-repairing bottom layer with a spray gun and cured at room temperature for 7 days to obtain a fully self-repairing anti-corrosion coating with high strength, long-term durability and excellent self-healing ability. After the coating is cured, the total thickness of the coating is measured with a coating thickness gauge, and the total thickness of the coating is 150 μm.

[0094] The performance of the fully self-repairing anti-corrosion coating with high strength, long-term durability and excellent self-healing ability obtained in Example 1 was tested, and the results are shown in Tables 1 and 2 below.

[0095] Table 1 EIS data fitting parameters of the cyclic self-repairing process of the fully self-repairing anti-corrosion coating

[0096]

[0097]

[0098] It can be seen from Table 1 that after the self-repairing anti-corrosion coating has undergone multiple damage / repair cycle experiments, its impedance |Z| f-0.01Hz Still above 10 10 , proving that the fully self-healing anti-corrosion coating has excellent self-healing and barrier properties.

[0099] Table 2 |Z| of coatings in sodium chloride solution with immersion time f-0.01Hz Change results

[0100]

[0101] It can be seen from Table 2 that the impedance |Z| of the fully self-repairing anti-corrosion coating after 250 days in a high-salt and high-humidity environment f-0.01Hz Still above 10 10 The fully self-repairing anti-corrosion coating has good durability, greatly extends the service life of the coating, and the product performance is good.

[0102] Figure 1 This is the self-repairing performance test of the elastomer PUE after scratching in Example 1. It can be seen that the coating can be quickly repaired in underwater salt solution and under large-scale damage, and its original barrier capacity can be restored; Figure 2 The self-repairing performance of the self-repairing bottom layer (100 μm) after scratching is introduced; Figure 3 It is introduced that after chemical modification, the hydrophobic property of the self-repairing anti-corrosion surface polymer is improved and the barrier ability is better enhanced; Figure 4 The combination of a self-repairing bottom layer (100 μm) and a self-repairing anti-corrosion surface layer (50 μm) is introduced to construct a fully repairable anti-corrosion coating. Even if it is a large-sized scratch, the fully self-repairing anti-corrosion coating can still self-repair after being scratched.

[0103] It can be seen from the above embodiments that the present invention provides a fully self-repairing anti-corrosion coating with high strength, long-term durability and excellent self-healing ability and a preparation method thereof. The present invention proposes the concept of full repair for the first time: 1) Zinc powder is mixed with polyurea with a hyperbranched structure to prepare a self-repairing bottom layer to achieve the purpose of sacrificial cathode protection of the anode; 2) The hyperbranched polyurea is grafted with a fluorine-containing polymer to achieve the purpose of barrier; 3) The active anti-corrosion bottom layer is combined with the passive anti-corrosion surface layer to achieve the purpose of full self-repair, and a fully self-repairing anti-corrosion coating with high adhesion and high durability is obtained. The present invention utilizes the bond exchange principle of dynamic bonds to achieve the self-repair of polyurea elastomers with hyperbranched structures, and the repair time for scratches is only 3.5h (room temperature) and has a relatively high strength (21.5MPa). It can resist mechanical damage such as water flushing and scratches, and at the same time has good durability in high-salt and high-humidity environments, greatly extending the service life of the coating.

[0104] The present invention constructs a double-layer coating based on high-performance hyperbranched polyurea. The self-repairing anodic protection primer and the hydrophobic topcoat provide rapid self-repairing capabilities while also providing excellent barrier and anti-corrosion capabilities, thereby constructing a fully self-repairing anti-corrosion coating with good performance, room temperature self-repairing capabilities, and long-term durability.

[0105] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a fully self-repairing anti-corrosion coating with high strength, long-term durability and excellent self-healing ability, characterized in that: The fully self-repairing anti-corrosion coating with high strength, long-term durability and excellent self-healing ability comprises a self-repairing bottom layer and a self-repairing anti-corrosion surface layer, and the preparation method comprises the following steps: 1) dissolving polyetheramine, polyethyleneimine, tris(2-aminoethyl)amine and polyvinyl alcohol in an organic solvent, and then adding an isocyanate curing agent to carry out a condensation polymerization reaction to obtain a first product PUE; 2) dissolving the first product PUE in an organic solvent to obtain a first dissolved substance solution; 3) mixing the first dissolved substance solution with zinc powder to obtain a second dissolved substance solution; 4) coating the second dissolved substance solution on the substrate, and obtaining a self-repairing bottom layer after curing; 5) mixing the first product PUE and the acrylic ester fluorine-containing polymer in an organic solvent, and then adding an initiator to carry out a free radical polymerization reaction to obtain a second product PUEF; 6) dissolving the second product PUEF in an organic solvent to obtain a third dissolved substance solution; 7) The third dissolved substance solution is coated on the base layer, and after curing, a self-repairing anti-corrosion surface layer is obtained.

2. The preparation method according to claim 1, characterized in that: The polyetheramine comprises polyetheramine D400 and polyetheramine D2000; The acrylate fluorine-containing polymer is obtained by free radical polymerization of fluorine-containing acrylate monomers and acrylate monomers in the presence of an initiator; The fluorine-containing acrylate monomer is 2,2,3,3,4,5,5,6,6,7,7-dodecafluoroheptyl acrylate, and the acrylate monomer comprises one of ethyl acrylate, methyl methacrylate and butyl acrylate; The isocyanate curing agent includes isophorone diisocyanate.

3. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of the polyetheramine, polyethyleneimine, tri(2-aminoethyl)amine and polyvinyl alcohol is 9000-10000:3-45:3-45:100-200, and the mass ratio of the isocyanate curing agent and the polyetheramine is 4-6:5-20.

4. The preparation method according to claim 3, characterized in that: The temperature of the free radical polymerization reaction is independently 60 to 80° C., and the reaction time is independently 20 to 28 hours.

5. The preparation method according to claim 4, characterized in that: The organic solvent independently comprises one or more of 1,4-dioxane, cyclohexanone, tetrahydrofuran, ethanol and propylene glycol methyl ether; The solid content of the first product PUE is 30-40%; The solid content of the second product PUEF is 30-40%.

6. The preparation method according to claim 1, 2 or 5, characterized in that: The solid content of the first solute solution is 30-40%, and the solid content of the third solute solution is 30-40%; the added amount of the zinc powder is 50-70% of the mass of the first product PUE.

7. The preparation method according to claim 6, characterized in that: The coating is spraying, and the thickness of the self-repairing bottom layer and the self-repairing anti-corrosion surface layer are independently 50-155 μm.

8. The preparation method according to claim 1 or 7, characterized in that: The mass ratio of the first product PUE to the acrylate fluorinated polymer is 10:30-50, and the content of the initiator is 0.2-1% of the mass of the acrylate fluorinated polymer; The initiator comprises azobisisobutyronitrile and / or dibenzoyl peroxide.

9. The preparation method according to claim 8, characterized in that: The curing is performed at room temperature, and the curing time is 2 to 7 days.

10. A fully self-repairing anti-corrosion coating with high strength, long-term durability and excellent self-healing ability prepared by the preparation method according to any one of claims 1 to 9.